Harmonic state estimation and localization based on broad-band measurement - Wu, Wei; Zeng, Dehui; Li, Jianghui; Lu, Jiajun; Li, Chaojie; Liu, Shenquan (Frontiers in Energy Research, 2023)
Harmonic and power quality issues brought by the high power electronics penetration level have become a rising threat to power grids. To achieve accurate measurement of the broadband harmonics caused by the power electronic devices, the broadband phasor measurement unit has been developed and installed. However, due to its high cost, it is less practical to install bPMU on each node, and therefore, how to obtain the global harmonic state in the power grid with minimum bPMUs is a crucial issue. This paper is focused on the harmonic state estimation method based on bPMU data. The mathematical model for harmonic state estimation is first derived based on circuit principles. Then, the weighted least squares method is then utilized to solve the established measurement equations for harmonic state estimation to obtain the harmonic state across the grid. Furthermore, the 0–1 integer programming approach is employed to optimize the installation locations of the bPMUs to reduce the overall cost while maintaining full observability. Subsequently, the harmonic sources are localized by analyzing the injected harmonic power on each node. Finally, the validity and effectiveness of the proposed method are proved by matching results between the proposed methods and the simulation model based on the IEEE 14-node system.